Thermal transformations in ultrafine plasmochemical zirconium dioxide powders; Journal of Thermal Analysis and Calorimetry; Vol. 119, iss. 3 - Surzhikov A. P. Anatoly Petrovich; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Vasiljev I. P. Ivan Petrovich (2015, 2015)
Title screen